2006
DOI: 10.1200/jco.2006.07.3916
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Adjuvant Epirubicin-Based and Docetaxel Chemotherapy for Node-Positive Breast Cancer Patients: The FNCLCC PACS 01 Trial

Abstract: Sequential adjuvant chemotherapy with FEC followed by docetaxel significantly improves disease-free and overall survival in node-positive breast cancer patients and has a favorable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
329
4
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(367 citation statements)
references
References 32 publications
21
329
4
13
Order By: Relevance
“…Several randomized trials have recently reported that adjuvant treatment with docetaxel or paclitaxel improves DFS in women with lymph-nodepositive breast cancer [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several randomized trials have recently reported that adjuvant treatment with docetaxel or paclitaxel improves DFS in women with lymph-nodepositive breast cancer [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…In the event of febrile neutropenia or grade 3 or 4 neutropenia, G-CSF [Filgrastim (Granocyte, Sanofi-Aventis) 5 lg Kg -1 day -1 on days [4][5][6][7][8][9][10][11] was administered in all subsequent chemotherapy cycles. If a second episode of grade 3 or 4 neutropenia or febrile neutropenia occurred despite the administration of G-CSF or in case of grade 3 or 4 thrombocytopenia, the doses of all drugs were reduced by 20% in subsequent cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from invasive ductal carcinoma, medullary, metaplastic, secretory, pleomorphic lobular carcinomas, adenoid cystic carcinomas etc., also belong to triple negative tumours. The main characteristics of triple negative breast cancers are they are frequent in younger women (<50 years), more frequent in AfricanAmerican women, present as interval cancers, highly chemosensitive [12,13], weak association between tumour size and lymph node metastases, more aggressive, higher chance of brain metastases, high chance of recurrence during 1 st and 3 rd year and shorter survival following first metastatic event when compared to other subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Later, anthracycline combinations were found to be slightly but significantly more effective than the CMF regimen [2]. More recently, several adjuvant phase III trials have shown that taxane regimens further reduce the likelihood of recurrence and death, compared to anthracycline-containing combinations [3][4][5][6][7][8][9][10], but the absolute benefit was again small, and some trials were unable to show any advantage for the taxane arm [11,12]. Taxanes and anthracyclines can induce some acute and chronic toxicities of considerable clinical concern.…”
Section: Introductionmentioning
confidence: 99%